Aprovechar la toma de decisiones dinámica y el análisis ambiental para respaldar experiencias de aprendizaje auténticas en entornos digitales - Stefaniak, Jill; Xu, Meimei (Revista de Educación a Distancia (RED), 2020)
Authentic learning is a pedagogical approach that situates students in real-world settings. Authentic learning experiences in online environments allow learners to solve real-world problems when they immerse in real-world settings. It thereby requires instructional designers to make contextualized design decisions to enhance students’ online authentic learning experiences. The purpose of this paper is to provide instructional designers with a conceptual framework to help guide their instructional design decisions for authentic learning experiences in online environments. We purport that these design decisions should be guided by three constructs: authentic learning, decision-making, and contextual analysis. We also provide recommendations for future research on decision-making practices and processes in instructional design contexts.